The corporate social responsibility overview. - Mohd Radzi, Naziatul Aziah; Yahya, Salleh; Azman Aziz, Mukhriz Izraf (Universiti Sains Malaysia, 2014)
Corporate Social Responsibility (CSR) is a tool for companies to show their commitment towards social issues when the corporate involvement could strengthen the continuity and company’s operation while at the same time to show their existence in the community. Essentially, CSR is corporate involvement in social activities in which their role is very important to improve the quality of social life in terms of education, health and environmental sustainability.